AtlantOS data products from multibeam EM122 data: METEOR cruise M139 (Atlantic) - Wölfl, Anne-Cathrin; Schade, Martin (PANGAEA, 2018)
The multibeam raw data has been cleaned, quality assured and processed using QPS Qimera. Data products include ungridded soundings and bathymetric grids (100 m resolution). The data processing and provision took place within the EU Horizon 2020 project AtlantOS - Optimising and Enhancing the Integrated Atlantic Ocean Observing Systems. For map of transit track see: https://doi.org/10.1594/PANGAEA.881298
Keywords: Bathymetry